The Productive Parameters and cost benefit Analysis of growing Rabbits Fed cooked Bambara groundnut meal in the semi- arid zone of Nigeria - Y., Usman; h., Husa; S. Z., Yusuf; A. M, Dunya; M.M, Njiti (International Journal of Environment, Agriculture and Biotechnology, 2019)
A ten-weeks feeding trial was conducted to determine the effect of replacing groundnut cake (GNC) with cooked Bambara nut meal (CBNM) on the performance of growing rabbits. Thirty mixed breed (New Zealand White X Dutch) of rabbits six to seven weeks of age with average initial body weight of 604.50 g were caged individually and allotted to five (5) dietary treatments. Each treatment had six (6) replications. The rabbits were given diets and clean drinking water ad libitum throughout the period of experimentation. In diets 1(control), 2, 3, 4 and 5 CBNM replaced GNC at 0%, 25%, 50%, 75% and 100%, respectively. The productive parameters measured include; feed intake, weight gain, feed conversion ratio. All data collected in the course of the experiment were subjected to analysis of variance (ANOVA) using the completely randomized design (Steel and Torrie, 1980) and where applicable Duncan’s multiple range test, was used for mean separation, while analysis of economics of production was carried out based on the prevailing market prices of feed ingredients at the time of study. The cost per kilogram of each test diet, the cost of feeding rabbits on the test diets throughout the period of the experiment and the cost per kilogram of weight gained by the rabbits were used in assessing the economics of replacing different levels of groundnut cake with cooked Bambara nut meal. Daily feed intake was significantly (P<0.05) different among treatment groups with the control (0% CBNM) consuming more feed than those on different levels of CBNM. Daily feed intakes were 69.07 g, 59.51 g, 61.51 g, 60.53 g and 62.99 g for rabbits on the 0%, 25%, 50%, 75% and 100% CBNM levels, respectively. There were no significant difference (P>0.05) among treatments groups in weight gain, feed conversion ratio (FCR) and Use of CBNM as replacement for GNC resulted into a savings of at least ₦46.00 when 100% CBNM and up to ₦72.00 when 50% CBNM was used instead of GNC in growing rabbits’ diets. It was concluded that CBNM can replace up to 50% of the GNC in the diets of growing rabbits for optimum economic benefit.